An introduction to drugs in sport. : Addicted to winning? - Waddington, Ivan.; Smith, Andy. (New York : London : Routledge, 2009)
Why do many athletes risk their careers by taking performance-enhancing drugs? Do the highly competitive pressures of elite sports teach athletes to win at any cost? This book examines drug use in sport and attempts to explain why athletes have over the years used performance-enhancing drugs
Includes bibliography references and index.
Keywords: Doping in sports